Delusions of a Magic Man Shared by Codependent Twin Sisters - Shaikh, Anam; Lai, Randy (Case Reports in Psychiatry, 2022)
Folie à deux has been called double insanity or shared psychotic disorder. In this report, we describe the case of twin sisters who presented with identical delusions. Both sisters reported a “magic man” lived in their bodies and made them weak. Both underwent treatment with similar medications: the primary case with risperidone and the secondary case with paliperidone. The delusions of the primary case slowly abated with antipsychotics, whereas those of the secondary case completely resolved within a short duration after admission when the twins were separated in different hospital units.